Public Sphere and Post-populism in the COVID-19 Pandemic: The Short Life of Depolarisation in Argentina - Peruzzotti, Enrique; Waisbord, Silvio (Javnost-The Public, 2021)
In this article, we examine whether the COVID-19 pandemic opens opportunities for consensual politics and the reconstruction of a pluralistic public sphere in countries characterised by polarised politics. Our focus is on how the Alberto Fernández administration in Argentina managed the crisis during 2020 and the window of opportunity that the pandemic created for a post-populist, depolarised scenario. Although the government initially tried to pursue consensual policymaking and foregrounded a public health response to the crisis, the prolonged nature of the health crisis, the toll of the pandemic, and the failure of government policies to address multiple aspects of the crisis reactivated political polarisation. The Argentine case helps to understand whether the politics of depolarisation amid the pandemic are possible and sustainable. Even with scientific expertise gaining significant presence, legitimacy and initial consensus, it is insufficient to chart out a path to depolarisation given persistent structural dynamics that foster sharp divisions.